Prognosis of Neonatal Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
The neurologic outcome of 40 infants with EEG documented seizures of diverse etiologies was examined retrospectively at the Division of Neurology, The Children's Hospital of Philadelphia, PA.